Modelling the effect of beliefs about asthma medication and treatment intrusiveness on adherence and preference for once-daily vs. twice-daily medication. (December 2017) - Chapman, Sarah; Dale, Peter; Svedsater, Henrik; Stynes, Gillian; Vyas, Nicola; Price, David; Horne, Rob
Abstract People with asthma who do not adhere to their maintenance medication may experience poorer asthma control and need more healthcare support than those who adhere. People (N = 1010) aged 18–55 years with self-reported asthma, taking one or more asthma maintenance medication(s), from five European countries, participated in a survey using validated scales (Medication Adherence Report Scale [MARS], Asthma Control Test™ [ACT], Beliefs about Medicine Questionnaire [BMQ] and the Asthma Treatment Intrusiveness Questionnaire [ATIQ]). We performed a post hoc evaluation of adherence to maintenance medication, asthma control, beliefs about medication, preferences for once-daily vs. twice-daily asthma maintenance medication and treatment intrusiveness, using structural equation modelling to investigate the relationships between these factors. Most participants reported potential problems with asthma control (ACT < 19: 76.8% [n = 776]), low adherence (median MARS = 3.40) and preferred once-daily medication (73.5% [n = 742/1010]). Non-adherence was associated with worse asthma control (r = 0.262 [P < 0.001]) and a expressed preference for once-daily medication over a "twice daily medication that works slightly better" (test statistic [T ] = 2.970 [P = 0.003]). Participants reporting non-adherence/preferring once-daily medication had negative beliefs about their treatment (BMQ necessity-concerns differential:r = 0.437 [P < 0.001]/T = 6.886 [P < 0.001]) and found medication intrusive (ATIQ:r = −0.422 [P < 0.001]/T = 2.689[P = 0.007]). Structural equation modelling showed complex relationships between variables, including: (1) high concerns about treatment associated with increased perceived treatment intrusiveness and reduced adherence, which influenced asthma control; (2) high concerns about treatment and healthcare seeking behaviour, which were predictive of preferring twice-daily asthma medication. Concerns about medication and perceived treatment intrusiveness were predictive of poor adherence, and were associated with preference for once-daily asthma medication. Confirm the utility of the PAPA model and NCF in explaining nonadherence linked to poor asthma control. Asthma: Examining beliefs around maintenance medication Encouraging adherence to maintenance medication for asthma requires a dual approach that considers patient perceptions as well as practicalities. While doctors may prescribe patients with appropriate medication to control asthma, many patients do not adhere to their maintenance regime. The reasons for this are complex, revolving around patient beliefs about long-term medication. Robert Horne at University College London, UK, and co-workers modelled data collected from interviews with 1010 adult patients from five European countries. Over a quarter of patients reported non-adherence and this was linked to concerns about ICS and perceived treatment intensiveness. Patients' beliefs about ICS and the concept of medication 'intrusiveness' were key factors in non-adherence. Understanding individual patient goals, eliciting patient concerns and addressing practical barriers should help encourage adherence.